PENDIDIKAN NILAI DALAM MEMANUSIAKAN MANUSIA - Jeditia Taliak (IAKN Ambon, 2018)
Education in human development and humanizing human beings is certainly expected to be done through the education process (school) which is followed by the students in particular but also for society in general. Society as a supporter and implementer of education itself must provide motivation. therefore, through educational institutions (schools) both public and private, society in general, but also learners are equipped with